2023
DOI: 10.3389/fpls.2023.1225445
|View full text |Cite
|
Sign up to set email alerts
|

Genomic landscape of the OsTPP7 gene in its haplotype diversity and association with anaerobic germination tolerance in rice

Abstract: Early season flooding is a major constraint in direct-seeded rice, as rice genotypes vary in their coleoptile length during anoxia. Trehalose-6-phosphate phosphatase 7 (OsTPP7, Os09g0369400) has been identified as the genetic determinant for anaerobic germination (AG) and coleoptile elongation during flooding. We evaluated the coleoptile length of a diverse rice panel under normal and flooded conditions and investigated the Korean rice collection of 475 accessions to understand its genetic variation, populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 86 publications
0
1
0
Order By: Relevance
“…Because of the shortage of fresh water and labor resources as well as the increase of input cost, direct seeding became a major method for rice production (Aung et al 2023;Miro and Ismail 2013) and the ability of rice cultivars to develop a long coleoptile under flooded water is significant. Many previous studies indicated that this ability of japonica rice varieties was better than indica one (Aung et al 2023;Nghi et al 2019;Su et al 2021;Zhang et al 2017). However, our results showed a high coleoptile elongation capacity of indica accession.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the shortage of fresh water and labor resources as well as the increase of input cost, direct seeding became a major method for rice production (Aung et al 2023;Miro and Ismail 2013) and the ability of rice cultivars to develop a long coleoptile under flooded water is significant. Many previous studies indicated that this ability of japonica rice varieties was better than indica one (Aung et al 2023;Nghi et al 2019;Su et al 2021;Zhang et al 2017). However, our results showed a high coleoptile elongation capacity of indica accession.…”
Section: Discussionmentioning
confidence: 99%